An automated system for continuous monitoring of CO2 geosequestration using multi-well offset VSP with permanent seismic sources and receivers: Stage 3 of the CO2CRC Otway Project. (June 2021) - Isaenkov, Roman; Pevzner, Roman; Glubokovskikh, Stanislav; Yavuz, Sinem; Yurikov, Alexey; Tertyshnikov, Konstantin; Gurevich, Boris; Correa, Julia; Wood, Todd; Freifeld, Barry; Mondanos, Michael; Nikolov, Stoyan; et al.
Highlights: Continuous offset VSP for CO2 injection monitoring deployed at CO2CRC Otway site. Downhole DAS with engineered fibres combined with permanent SOV sources. Automated data processing reduces data volumes from terabytes to megabytes. Setup evaluated using over 100 days of baseline data. Borehole seismic geometry allows for high repeatability; NRMS ∼ 10–15 %. Abstract: A permanent automated continuous seismic CO2 geosequestration monitoring system for was installed at CO2CRC Otway Project site (Victoria, Australia) in early 2020. The system is composed of five deviated ∼1600 m deep wells equipped with distributed acoustic sensing (DAS) acting as seismic receivers and nine seismic orbital vibrators (SOV) as seismic sources. DAS recording is performed continuously by three iDASv3 units. Each SOV operates for 2.5 h at a time, and hence all SOVs operating sequentially (during daytime only) produce in a single vintage every two days. Each vintage consists of 45 offset VSP transects covering predicted CO2 plume migration paths over ∼0.7 km 2 area. An automated data processing implemented on-site reduces data size from ∼1.3 TB/day to ∼500 MB/day with the results transmitted to the office daily. The repeatability analysis based on pre-injection data (acquired from May to October 2020 before the injection start in December 2020) shows that variability of SOV performance is the main source of non-repeatability while borehole measurements are stable. An SOV waveform could reach NRMS value from 20 to 100 % within a few days. However, deconvolution of the seismograms with the waveform of the direct wave reduces the repeatability to within 10–15 % NRMS.